2006
DOI: 10.1038/sj.bjp.0706467
|View full text |Cite
|
Sign up to set email alerts
|

Bv8, the amphibian homologue of the mammalian prokineticins, induces a proinflammatory phenotype of mouse macrophages

Abstract: 1 The small protein Bv8, isolated from the amphibian skin, belongs to a novel family of secreted proteins linked to several biological effects. We describe the expression of Bv8/prokineticins and their receptors in mouse macrophages, and characterize their proinflammatory activities. 2 The rodent analogue of Bv8, prokineticin-2, is expressed by macrophages, as well as its G-proteincoupled receptor prokineticin receptor (PKR-1 and PKR-2). PKR-1 is expressed more abundantly. 3 Bv8 induces potent chemotaxis of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
139
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(150 citation statements)
references
References 41 publications
10
139
1
Order By: Relevance
“…In cardiac tissue, Bv8 was able to attenuate cardiomyocyte oxidative stress (Urayama et al, 2008) and, in a very recent report, a novel PKR1 agonist was demonstrated to prevent myocardial infarction in mice via an angiogenic mechanism (Gasser et al, 2015). However, reports also exist showing that Bv8/PK2 prokineticins induce a proinflammatory phenotype in mouse macrophages (Martucci et al, 2006), exacerbate the infarct volume in rats subjected to transient or permanent cerebral focal ischemia (Cheng et al, 2012), or reduce cell viability in primary rat cortical cultures (Severini et al, 2015). In these latter studies, prokineticin receptor blockers were able to protect against post-ischemic cell death (Cheng et al, 2012) or amyloid beta-induced neurotoxicity (Severini et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In cardiac tissue, Bv8 was able to attenuate cardiomyocyte oxidative stress (Urayama et al, 2008) and, in a very recent report, a novel PKR1 agonist was demonstrated to prevent myocardial infarction in mice via an angiogenic mechanism (Gasser et al, 2015). However, reports also exist showing that Bv8/PK2 prokineticins induce a proinflammatory phenotype in mouse macrophages (Martucci et al, 2006), exacerbate the infarct volume in rats subjected to transient or permanent cerebral focal ischemia (Cheng et al, 2012), or reduce cell viability in primary rat cortical cultures (Severini et al, 2015). In these latter studies, prokineticin receptor blockers were able to protect against post-ischemic cell death (Cheng et al, 2012) or amyloid beta-induced neurotoxicity (Severini et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms are also possible: for example, the hyperalgesic effects of very low (femtomolar) concentrations of Bv8 are at least partly mediated by activation of the TRPV1 receptor , which has been shown to produce toxic effects and exacerbate OGD injury in our organotypic hippocampal slices (Landucci et al, 2011). Because of the absence of a vascular system and inflammatory cells in cortical cell or hippocampal slice cultures, other possible mechanisms known to be triggered by prokineticins, such as the pro-inflammatory (Martucci et al, 2006;Cheng et al, 2012) or angiogenic (LeCouter and Ferrara, 2003;Monnier and Samson, 2010) effects, can be ruled out in our experimental models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of PKRs in primary afferent C fibers sensitizes nociceptors to thermal, mechanical, and chemical stimuli (14)(15)(16). In neutrophils, macrophages, and dendritic cells it promotes chemotaxis and cytokine release (17)(18)(19)(20), and in capillary endothelial cells it stimulates angiogenesis (21). Testis, peripheral blood leukocytes, and macrophages express two mRNA transcripts of PK2, one coding for the canonical PK2 and the other for an elongated form containing additional 21 basic amino acids between Lys-47 and Val-48 of the mature PK2 protein, named PK2L (6,19,22).…”
mentioning
confidence: 99%